Ilala palm (Hyphaene petersiana) use in southern Zimbabwe: social and ecological factors influencing sustainability - Foote, A.L.; Krogman, N.T.; Grundy, I.M.; Nemarundwe, N.; Campbell, Bruce M.; Gambiza, J.; Gibbs, L. (2003)
A dynamic ecological model, calibrated with field data from the communal lands of southern Zimbabwe where Shangaaan and Ndebele people live, shows the ilala palm, Hyphaene petersiana, to be resilient to a wide range of harvesting regimes. The degree of use determines the plant population structure but not the palm's continued existence. Ilala palm sap for wine and leaves for crafts provide an important source of income at the village level. Shangaan households generally regulated palm use, with the manual workers usually being Ndebele. Despite the designation of the region as a "communal area" there are clearly social conventions limiting access to resources. The use of the plant for sap is more closely regulated than its use for leaves. Leaf harvests appear less ecologically destructive than tapping for sap. Although social rules reduce harvesting, the ecology of the palm is such that intensive harvesting may actually increase the available products by chaning the ilala palms into more accessible and useful growth form.